Neurologic Complications of Fetal Cocaine Exposure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Cocaine-positive urine toxicology at birth in 51 newborns was associated with hypertonia during infancy in 21(41%) studied at the Harlem Hospital Center, New York.